Die Menschheitsfamilie und der Begriff der Umma – Islamische Perspektiven im interreligiösen Dialog - Abdelrahem, Mohammed

"Komparative Theologie und Soziale Arbeit?!" - Lebock, Sarah
BloKK-Beitrag für das ZeKK, 11.07.2025

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, Moritz; Holtkamp, Pia Katharina; Hoyer, Kay-Peter; Kappe, Fabian; Yildiz, Safak; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (The Journal of Materials: Design and Applications, Part L)
One of the most important strategies for reducing CO2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.
Keywords: aluminium; casting; microstructure; joinability; self-piercing riveting

Analysis of the binding mechanisms depending on versatile process variants of self-piercing riveting - Lüder, Stephan; Holtkamp, Pia Katharina; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson; Lechner, Michael; Schmale, Hans Christian (Materials Research Proceedings)
The constantly increasing demand for climate protection and resource conservation requires innovative and versatile joining processes that improve adaptability to the joining task and robustness to enable flexible manufacturing on a production line. Therefore, the versatile SPR (V-SPR) and tumbling SPR (T-SPR) were developed. Using the example of a mixed material combination HCT590X+Z (t0 = 1.0 mm) / EN AW-6014 T4 (t0 = 2.0 mm), these processes were examined and compared with regard to the binding mechanisms form closure and force closure using micrographs, non-destructive resistance measurements and destructive torsion tests. For this purpose, a new sample geometry was defined, and the methods were adapted to the SPR process variants.
Keywords: Joining; Self-Piercing Riveting; Sheet Metal

Validation and Verification of Novel Three-Dimensional Crack Growth Simulation Software GmshCrack3D - Krome, Sven; Duffe, Tobias; Kullmer, Gunter; Schramm, Britta; Ostwald, Richard (Applied Sciences)
The accurate prediction of crack initiation and propagation is essential for assessing the structural integrity of mechanically joined components and other complex assemblies. To overcome the limitations of existing finite element tools, a modular Python framework has been developed to automate three-dimensional crack growth simulations. The program combines geometric reconstruction, adaptive remeshing, and the numerical evaluation of fracture mechanics parameters within a single, fully automated workflow. The framework builds on open-source components and remains solver-independent, enabling straightforward integration with commercial or research finite element codes. A dedicated sequence of modules performs all required steps, from mesh separation and crack insertion to local submodeling, stress and displacement mapping, and iterative crack-front update, without manual interaction. The methodology was verified using a mini-compact tension (Mini-CT) specimen as a benchmark case. The numerical results demonstrate the accurate reproduction of stress intensity factors and energy release rates while achieving high computational efficiency through localized refinement. The developed approach provides a robust basis for crack growth simulations of geometrically complex or residual stress-affected structures. Its high degree of automation and flexibility makes it particularly suited for analyzing cracks in clinched and riveted joints, supporting the predictive design and durability assessment of joined lightweight structures.

Numerical investigation of pitting corrosion in clinched joints - Harzheim, Sven; Chen, Chin; Hollmer, Katharina; Hofmann, Martin; Zimmermann, Martina; Wallmersperger, Thomas (Acta Mechanica)
The effect of corrosion on mechanically joined components is not well understood. While recent research shows that a brief exposure of clinched specimens to a salt spray environment improves the specimens’ fatigue life, other research shows a decrease in load bearing capabilities with increasing corrosion times. These studies primarily focus on galvanic corrosion. It is not entirely clear how other corrosion phenomena, such as pitting corrosion, affect the fatigue life of clinched joints. In this work, a numerical model is used, which is able to simulate corrosion pit growth in EN AW-6014. The experimental polarization data of EN AW-6014 are used directly in the calculation of the interface kinetics parameter of the model.

Investigation of the impact of a rotationally superimposed punch stroke on the binding mechanisms of a clinched joint - Lüder, Stephan; Wolf, Eugen; Schmale, Hans Christian; Brosius, Alexander (MATEC Web of Conferences)
This paper examines the impact of a rotationally superimposed punch stroke on the binding mechanisms of clinched joints of aluminum sheets. As part of the development of a method for ensuring the versatility of clinching, an additional rotational movement of the punch was introduced as a control variable to influence friction in the mechanical joining process. The effect of rotational superimposition on the force-displacement curve of the clinching processes was investigated using four test variants with different kinematics. The primary objective was to evaluate the binding mechanisms that maintain the integrity of the clinched joint. To evaluate the force closure of the resulting joint, two testing methods were employed throughout the course of the research, non-destructive resistance measurement using four-wire sensing method and destructive torsion testing. A crucial factor influencing the efficacy of the process is surface cleanliness, as contaminants between joining partners can impede the effectiveness of the clinched joint. Therefore, all specimens were meticulously cleaned prior to experimentation. This method exhibits promising potential in creating clinched joints that align with the demands of flexible manufacturing environments.
Keywords: Joining; Sheet Metal; Tribology; Clinching

Bericht: Ressourcen für Resilienz in islamischer Tradition. Theologische, ethische und mystische Perspektiven - Kokew, Stephan Matthias; Al-Daghistani, Raid (Cibedo-Beiträge)

Innovationen im Kerncurriculum Spanisch : Lexiko-Grammatik im Fokus - Bürgel, Christoph (Niedersächsi- sches Kultusministerium (Hrsg.))

Fremdsprachenlehren und -lernen im Spannungsfeld von digital und analog - Bürgel, Christoph; Inal, Benjamin (Fremdsprachenlehren und -lernen im Spannungsfeld von digital und analog)

Unidades fraseológicas - ¿qué si no? Phraseologische Sprachbewusstheit entwickeln, in: Der Fremdsprachliche Unterricht Spanisch - Bürgel, Christoph

Förderung der mündlichen Sprachproduktion im Fremdsprachenunterricht. Perspektiven aus Wissenschaft und Praxis, in: bzf 69, 85-88. - Bürgel, Christoph; Schlaak, Claudia; Willems, Aline

- Digitalisierung als Wunderwaffe - Bürgel, Christoph; Siepmann, Dirk (FAZ)

 Zeitschrift für Romanische Sprachen und ihre Didaktik, ( Zeitschrift für Romanische Sprachen und ihre Didaktik)

AuroraFlow, an Easy-to-Use, Low-Latency FPGA Communication Solution Demonstrated on Multi-FPGA Neural Network Inference - Pape, Gerrit; Wintermann, Bjarne; Jungemann, Linus; Lass, Michael; Meyer, Marius; Riebler, Heinrich; Plessl, Christian (Proceedings of the 15th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies)

Evaluating the Strong Scaling Potential of AI Engines for Molecular Dynamics Simulations - Bröker, Mika; Menzel, Johannes; Plessl, Christian (Proceedings of the 15th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies)

Experimental and numerical investigation of the influence of rolling-induced sheet metal deformation on SPR joints - Schlichter, Malte Christian; Harabati, Özcan; Ludwig, Jean-Patrick; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the development of advanced lightweight automotive solutions, self-piercing riveting (SPR) offers the possibility of joining multi-material structures to fulfil a wide variety of requirements. With regard to the entire process chain, production-related pre-deformations of the parts to be joined can influence the geometric shape and load capacity of SPR joints. Various studies have investigated the influence of pre-stretched sheet materials, in the sense of pre-drawing processes, on the formation of SPR joints. The impact of pre-stretching sheet metals on the formation of their geometrical characteristics and the shear-tensile strength of SPR processes was observed [1]. Pre-rolled semi-finished products are also joined together in mixed material automotive structures, e.g. tailor rolled blanks. This work aims to investigate the influence of pre-rolled joining parts on the geometric formation and load-carrying capacity of SPR joints. For this purpose, sheets of metal are cold-formed using a rolling process to induce a defined strain-hardening state in the material and then joined in various combinations. As the degree of deformation increases, the rolling of samples can lead to minimal accumulation of damage in the sheet materials, which can influence the joint behaviour. The rolling process, as well as the subsequent joining process, are also investigated by FEM. The influence of pre-rolled semi-finished products on the strength of the SPR joints is investigated.

Resonant and antiresonant exciton-phonon coupling in quantum dot molecules - Lienhart, Michelle; Gawarecki, Krzysztof; Stöcker, Markus; Bopp, Frederik; Cullip, Charlotte; Akhlaq, Nadeem; Thalacker, Christopher; Schall, Johannes; Rodt, Sven; Ludwig, Arne; Reuter, Dirk; Reitzenstein, Stephan; et al. (Physical Review B)
Spins confined in optically active quantum dot molecules (QDMs) can be used for the deterministic generation of photonic graph states with tailored entanglement structures. Their usefulness for the generation of such nonclassical states of light is determined by orbital and spin decoherence mechanisms, particularly phonon-mediated processes dominant at energy scales up to a few millielectronvolts. Here, we directly measure the spectral function of orbital phonon relaxation between the energy states of the neutral exciton in a QDM and benchmark our findings against microscopic <a:math xmlns:a="http://www.w3.org/1998/Math/MathML"> <a:mrow> <a:mi mathvariant="bold-italic">k</a:mi> <a:mo>·</a:mo> <a:mi mathvariant="bold-italic">p</a:mi> <a:mspace width="4pt"/> </a:mrow> </a:math> theory. Our results reveal pronounced resonances and antiresonances in the phonon-relaxation rates, ranging from tens of <e:math xmlns:e="http://www.w3.org/1998/Math/MathML"> <e:mrow> <e:mi>µ</e:mi> <e:msup> <e:mrow> <e:mi mathvariant="normal">s</e:mi> </e:mrow> <e:mrow> <e:mo>−</e:mo> <e:mn>1</e:mn> </e:mrow> </e:msup> </e:mrow> </e:math> up to tens of <g:math xmlns:g="http://www.w3.org/1998/Math/MathML"> <g:msup> <g:mrow> <g:mi>ns</g:mi> </g:mrow> <g:mrow> <g:mo>−</g:mo> <g:mn>1</g:mn> </g:mrow> </g:msup> </g:math> . Comparison with a kinetic model reveals the voltage (energy) dependent phonon coupling strength and fully explains the interplay between phonon-assisted relaxation and radiative recombination. The resonances and antiresonances enable further tunability of the exciton lifetime which can be leveraged to increase the lifetime of energetically unfavorable charge configurations needed for realizing efficient spin-photon interfaces and multidimensional cluster states.

Quantum 2-SAT on low dimensional systems is $\mathsf{QMA}_1$-complete: Direct embeddings and black-box simulation - Rudolph, Dorian; Gharibian, Sevag; Nagaj, Daniel (16th Innovations in Theoretical Computer Science (ITCS))
Despite the fundamental role the Quantum Satisfiability (QSAT) problem has played in quantum complexity theory, a central question remains open: At which local dimension does the complexity of QSAT transition from "easy" to "hard"? Here, we study QSAT with each constraint acting on a $k$-dimensional and $l$-dimensional qudit pair, denoted $(k,l)$-QSAT. Our first main result shows that, surprisingly, QSAT on qubits can remain $\mathsf{QMA}_1$-hard, in that $(2,5)$-QSAT is $\mathsf{QMA}_1$-complete. In contrast, $2$-SAT on qubits is well-known to be poly-time solvable [Bravyi, 2006]. Our second main result proves that $(3,d)$-QSAT on the 1D line with $d\in O(1)$ is also $\mathsf{QMA}_1$-hard. Finally, we initiate the study of 1D $(2,d)$-QSAT by giving a frustration-free 1D Hamiltonian with a unique, entangled ground state. Our first result uses a direct embedding, combining a novel clock construction with the 2D circuit-to-Hamiltonian construction of [Gosset, Nagaj, 2013]. Of note is a new simplified and analytic proof for the latter (as opposed to a partially numeric proof in [GN13]). This exploits Unitary Labelled Graphs [Bausch, Cubitt, Ozols, 2017] together with a new "Nullspace Connection Lemma", allowing us to break low energy analyses into small patches of projectors, and to improve the soundness analysis of [GN13] from $Ω(1/T^6)$ to $Ω(1/T^2)$, for $T$ the number of gates. Our second result goes via black-box reduction: Given an arbitrary 1D Hamiltonian $H$ on $d'$-dimensional qudits, we show how to embed it into an effective null-space of a 1D $(3,d)$-QSAT instance, for $d\in O(1)$. Our approach may be viewed as a weaker notion of "simulation" (à la [Bravyi, Hastings 2017], [Cubitt, Montanaro, Piddock 2018]). As far as we are aware, this gives the first "black-box simulation"-based $\mathsf{QMA}_1$-hardness result, i.e. for frustration-free Hamiltonians.

Sprachbezogene Kompetenzerwartungen im Sportunterricht – Eine systematische Lehrplananalyse - Grimminger-Seidensticker, Elke; Treder, Alexandra; Niederhaus, Constanze (Zeitschrift für Sportpädagogische Forschung)